(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Active transport (AT) is a key component of sustainable development, serving as both a strategy for mitigating climate change and a means of promoting physical activity and overall health. Effective school sustainability policies have the potential to significantly improve the health of students and contribute to planetary wellbeing. The aim of this study is investigating the effects of school sustainable environments on active transport’s attitudes and intention. Methods: A cross-sectional study was conducted involving 1,005 students aged 16–19 years (mean age 16.1, standard deviation 1.15), with 54% female participants. Three items assessing perceptions of sustainability education, support for AT, and the presence of AT infrastructure within the school environment were combined to form a single ‘School Sustainable Environment’ factor. Items aligned with the Theory of Planned Behaviour were used to measure sustainability-related attitudes (7 items), active transport-related attitudes (5 items), sustainability-related subjective norms (4 items), active transport-related subjective norms (4 items), perceived behavioural control (4 items), and intention for AT (7 items). AT behaviour was assessed using a subscale from the Global Physical Activity Questionnaire (GPAQ; 3 items). Age, gender, and ownership of non-motorised vehicles were included as control variables. Linear regression analyses were performed to examine the relationships between predictor variables and outcomes. Mediation analysis was conducted using the PROCESS macro. Results: The findings indicate a significant relationship between the school sustainable environment and both sustainability-related and active transport-related subjective norms, as well as perceived behavioural control (standardised beta coefficients ranged from .531 for perceived behavioural control to .583 for the sustainability-related subjective norm). The intention to use AT was significantly predicted by the active transport-related subjective norm (std. β = .244, p < .001) and perceived behavioural control (std. β = .533, p < .001). This intention, in turn, was associated with AT behaviour (std. β = .106, p = .021). Mediation analysis revealed that the active transport-related subjective norm and perceived behavioural control mediated the relationship between the school sustainable environment and intention to use AT. Conclusion: The school environment plays a pivotal role in indirectly encouraging AT among students by directly cultivating a sustainability-focused mindset and offering infrastructure that supports active commuting.